2012
DOI: 10.1186/1480-9222-14-4
|View full text |Cite
|
Sign up to set email alerts
|

A microplate technique to simultaneously assay calcium accumulation in endoplasmic reticulum and SERCA release of inorganic phosphate

Abstract: Traditional analyses of calcium homeostasis have separately quantified either calcium accumulation or release mechanisms. To define the system as a whole, however, requires multiple experimental techniques to examine both accumulation and release. Here we describe a technique that couples the simultaneous quantification of radio-labeled calcium accumulation in endoplasmic reticulum (ER) microsomes with the release of inorganic phosphate (Pi) by the hydrolytic activity of sarco-endoplasmic reticulum calcium ATP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Activity of sarco/endoplasmic Ca 2+ ATPase (SERCA), the main SR Ca 2+ pump of skeletal muscle, was estimated in SR isolated membranes from gastrocnemius by using a colorimetric assay that quantifies the amount of inorganic phosphate (P i ) that complexes with ammonium molybdate and malachite green following release from SERCA-mediated ATP hydrolysis [ 43 , 44 ]. Briefly, the reagent to quantify P i was prepared by mixing 1 vol of 10% (w/v) ammonium molybdate in 4 M HCl with 3 vol 0.2% (w/v) malachite green in 4 M HCl.…”
Section: Methodsmentioning
confidence: 99%
“…Activity of sarco/endoplasmic Ca 2+ ATPase (SERCA), the main SR Ca 2+ pump of skeletal muscle, was estimated in SR isolated membranes from gastrocnemius by using a colorimetric assay that quantifies the amount of inorganic phosphate (P i ) that complexes with ammonium molybdate and malachite green following release from SERCA-mediated ATP hydrolysis [ 43 , 44 ]. Briefly, the reagent to quantify P i was prepared by mixing 1 vol of 10% (w/v) ammonium molybdate in 4 M HCl with 3 vol 0.2% (w/v) malachite green in 4 M HCl.…”
Section: Methodsmentioning
confidence: 99%
“…Underneath, a carefully placed clean microplate will gather the filtrate dripping from above, being that microsomes that accumulated 45 Ca 2+ are incapable of passing through the filter, due to their charge and size. added to the filter wells and 45 Ca 2+ accumulation is determined using a Wallac microbeta liquid scintillation counter [8].…”
Section: Radiolabeled Calcium Measuringmentioning
confidence: 99%
“…Intraluminal calcium is the prime regulator for ER function, which has also been studied concomitantly in microsomes by researchers in last decades. Using non-fluorescent methods such as radioactive labelling of calcium ions, extensive studies have been reported using rat brain microsomes (12,13), hepatic microsomes (14) and rabbit skeletal microsomes (15). All the aforementioned radioactive Ca 2+ uptake and release studies have been performed only for native channels and pumps present in the ER such as Sarcoplasmic reticulum Calcium ATPase (SERCA) and leak channels such as Ryanodine receptors (RyR1 and RyR2).…”
Section: Introductionmentioning
confidence: 99%